Constructive side-channel analysis and secure design : 9th International Workshop, COSADE 2018, Singapore, April 23-24, 2018, Proceedings /: 9th International Workshop, COSADE 2018, Singapore, April 23-24, 2018, Proceedings. (2018) - Unknown
No abstract available